Sarana Berfikir Ilmiah (Bahasa, Logika, Matematika dan Statistika) - Lisa Anggraini; Yeni Karneli; Puji Gusri Handayani (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
Right thinking requires means or tools of thinking. This means is certain, so scientific activity will not be maximized without the means of scientific thinking. Mastery of scientific tools is very important for scientists in order to carry out scientific activities properly. The type of writing in this article is literature revieu or literature, the data is described descriptively, so that it shows a scientific study that can be further developed. The results of this study are that the stages of scientific activity require tools in the form of scientific thinking tools. The means of scientific thinking serves only as a tool for humans to think scientifically in order to gain knowledge. Language is a means of communicating systematic ways of thinking in acquiring knowledge. Without language skills, a person will not be able to carry out scientific activities systematically and correctly. Logic as a means of scientific thinking directs humans to think correctly in accordance with the rules of correct thinking. Logic helps humans to think systematically which can be accounted for. If you want to do thinking activities correctly, you must use logical thinking rules. Logic can distinguish between correct thinking processes and incorrect thinking processes. Mathematics is a means of deductive thinking, so people can use statistics for inductive thinking. Deductive thinking and inductive thinking are needed to support correct scientific activities so that they will produce correct knowledge as well. Statistics should not be underestimated by people who want to be able to carry out scientific activities properly. Mastery of statistics is necessary for people who will draw valid conclusions. Statistics must be seen as equal to mathematics.